Improving the Listening Skills of the First Semester Students of PAI Program of Hamzanwadi Islamic Institute of Pancor through Watching English Movie - Syamsul Rizal; Masjudin Masjudin (Tarbawi, 2022)
This research was intended to know how the technique using watching English movie can improve listening skill of the students. The technique required the students to realize causes of their listening problems in order to find out appropriate way of improving listening comprehension. This research involved 35 first semester students of PAI Program of Hamzanwadi Islamic Institute of Pancor. The objective of the research is to apply watching English movie technique to improve the students’ listening skill. The method applied in this research was a classroom action research. The data of the research were gathered through observation checklist, questionnaire, and listening test. The finding showed that watching English movie technique was successful in improving students’ listening skill. The improvement could be seen from the improvement of students’ scores in listening test. Besides, the finding also showed that watching English movie technique can improve the students’ involvement and enhance their interest in learning English, especially in listening.